Prevention, diagnosis and treatment of tumor lysis syndrome - Piwoński, Michał; Żak, Klaudia; Niedobylski, Sylwiusz; Stanicki, Paweł (Journal of Education, Health and Sport, 2021)
Tumor lysis syndrome (TLS) is an acute, life-threatening condition that occurs either spontaneously or as a complication of cytoreductive antitumor therapy, and occurs in both children and adults. As a result of TLS, intracellular components are released into the extracellular space, leading to dysregulation of the body’s homeostasis due to the accumulation of uric acid, phosphate and potassium ions, and hypocalcemia, which may lead to cardiac arrhythmias, convulsions, or kidney failure.